Influence of laser irradiation on phase structure and strehgth of cubic boron nitride - Гончарук, Олексій Олександрович (Technology audit and production reserves, 2012)
Laser processing regimes for irradiation of cubic boron nitride at wavelength λ=1,06 mkm where strength characteristics and phase structure remain unchanged